Analisis Efektivitas Penggunaan Instrumen Derivatif Dalam Manajemen Risiko Keuangan - Pujiharta; Rina Nurjanah; Hartono; Johanes P Kumagaya; Suprianus Pian T.A (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyze and determine the effectiveness of the use of derivative instruments in financial risk management. This research approach collects data through literature studies, which involve reading literature from various sources including books, journals and reports using qualitative and deductive approaches. The findings in this study are that risk cannot be avoided but can be minimized, one thing that can minimize risk is derivative instruments. Derivative instruments are developed in order to manage financial risk. Therefore, there are four derivative instruments used as a company strategy in minimizing financial risk, namely options, forward contracts, future co ntracts, and swaps.